Development and validation of the Vi-Med® tool for medication review - Thi Ha Vo&, Tra Linh Hoang, Erwin Martinez Faller&, Dang Thoai Nguyen (Journal of Applied Pharmaceutical Science, 2020)
Clinical pharmacy practice in Vietnam is unregulated by standard procedures, thus motivating this study, which developed and validated a tool called Vi-Med® for use in supporting medication review (MR) in Vietnamese hospitals. Six clinical pharmacists from six hospitals used the tool, which comprises three forms: Form 1 for the collection of patient information, Form 2 for the implementation of MR, and Form 3 for the documentation of pharmacist interventions (PIs). The tool also comes with eight pre-identified drug-related problems (DRPs) and seven PIs. The pharmacists were asked to categorize 30 PI-associated scenarios under appropriate DRPs and corresponding interventions. Concordance among the pharmacists was assessed on the basis of agreement level (%) and Cohen’s kappa (κ). We also evaluated the user-friendliness of the tool using a four-point Likert scale. Concordance in the panel with respect to DRPs and PIs was substantial (κ = 0.76 and 80.4% agreement) and almost perfect (κ = 0.83 and 87.6% agreement), respectively. All the experts were satisfied with the structure and content of Vi-Med®. Five of them evaluated the tool as very suitable, very useful, and definitely fitting for everyday use. Vi-Med® satisfactorily achieved consistency and user-friendliness, enabling its use in daily clinical pharmacy practice.
Keywords: Medication review, pharmacist intervention, documentation, tools, Vietnam.